Rancang Bangun Sistem Pemesanan Produk Jasa Percetakan Berbasis Web Di CV. Fajar Advertising - Yuni Sania; Khairil Khairil; Achmad Fikri Sallaby (UNIVED Press, 2024)
Humans as technology users must be able to utilize currently available technology. With the help of technology and information using the web, an ordering system that can be done via the internet, which is often called the web, will facilitate the marketing reach of the services and products sold by the Company. Dawn Advertising. The aim of this research is to build a web-based product ordering system. The research method used is the system design method. which can be accessed by all parties who need information on purchasing products at the company. Fajar Advertising. The supporting programs used are Dreamweaver as a web editor, PHP as a programming language, and MySQL as a database storage system. The design of this system makes it easier to efficiently market printing products and services online without limitations on space and time. The author's suggestion is that the system can be used according to the company's needs. It is hoped that the development of the system will eventually make this program an online program.